IMPLEMENTASI SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2011 TENTANG PENEMPATAN PENYALAHGUNAAN NARKOTIKA DI DALAM LEMBAGA REHABILITASI MEDIS DAN REHABILITASI SOSIAL DI PENGADILAN NEGERI PEKANBARU - Albezsia Artiamar F S; Mexsasai Indra; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Law enforcement against narcotics crime has been carried out by law enforcement officers and has received a judge's decision in a court hearing. In the Supreme Court Circular Letter Number 3 of 2011 concerning the Placement of Narcotics Abuse in the Institute of Medical Rehabilitation and Social Rehabilitation, every narcotics addict and victim of narcotics abuse must undergo medical rehabilitation and social rehabilitation.The purpose of this thesis is: First, to find out the implementation of the Supreme Court Circular Letter Number 3 of 2011 concerning the placement of narcotics abuse in medical rehabilitation and social rehabilitation institutions in the Pekanbaru District Court. Second, to find out the inhibiting factors for the implementation of the Supreme Court Circular Letter Number 3 of 2011 concerning the placement of narcotics abuse in medical rehabilitation and social rehabilitation institutions in the Pekanbaru District Court.This type of research can be classified as a type of sociological legal research, because in this study the authors directly conduct research at the location or places that are examined to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru District Court, while the population and sample were all sections related to this research, the data sources used included primary data, secondary data and tertiary data, data collection techniques, namely interviews and literature studies.From the results of the research and discussion it can be concluded that, First, the Implementation of the Supreme Court Circular Letter Number 3 of 2011 in the Pekanbaru District Court has not been going well and maximally. Second, Obstacles in the Implementation of the Supreme Court Circular Letter Number 3 of 2011 in the Pekanbaru District Court, namely that doctors have not been checked or delayed for narcotics abusers before trial in court, the second is budgetary problems, and thirdly the lack of cooperation with other Pekanbaru agencies in providing a place that is feasible in carrying out rehabilitation because so far in Pekanbaru City the place to do rehabilitation is done at the Tampan Mental Hospital.Keywords: Narcotics – Abuser – Implementation – Rehabilitation.